The use of UAVs for remote sensing applications: Case studies in Cyprus - Themistocleous, Kyriacos; Agapiou, Athos; Lysandrou, Vasiliki; Hadjimitsis, Diofantos G. (My University, 2015)
Downloading of the abstract is permitted for personal use only.Unmanned aerial vehicles (UAVs) for use in remote sensing offer simple and affordable observation from the air. Due to the decreasing size of the sensors, receivers and antennas, it is now possible to create integrated low-Altitude airborne systems. Remote sensing technologies on a UAV platform are an efficient, non-invasive and low cost resource for the detection, documentation and monitoring of various environmental (both natural and cultural) features, in high resolution and quality. Different remote sensing techniques can be used alongside to the UAVs, such as field spectroscopy, multispectral cameras, infrared cameras and thermal cameras. This integration in terms of techniques and technologies, contributes further to more solid outcomes depending on the case study. The possibility of adding a variety of sensors to the basic UAV unit amplifies both the application cases and the results. Among the types of camera sensors that can be used with the UAVs are the visible spectrum cameras, the multi-spectral cameras and the hyperspectral cameras. These cameras can extract more detailed information since an entire spectrum is acquired from each pixel of the image. In this paper, various UAVs used for environmental and archaeological applications in different areas of Cyprus are presented.
Keywords: Cultural environment; Cyprus; Natural environment; Remote sensing; Spectroscopy; UAV